A heterogeneous redundancy method for flight control computer based on mutual exclusion and spin mechanism. Issue 1 (1st April 2022) - Chen, Chang; Yang, Xueqi; Zhang, Jing; Xu, Shunfan; Chai, Xudong; Hong, Yan
Abstract: In order to meet the requirements of high reliability and economy of space launch vehicle control system, a heterogeneous redundancy method of flight control computer based on mutual exclusion and spin mechanism is proposed in this paper. This method avoids common cause failure mode and improves hardware resource utilization efficiency by resolving redundancy. The reliability and economy of the launch vehicle control system can be improved without increasing the cost of volume and weight.